Advertisement

Advertisement

Advertisement

Sum

Find the root of the following quadratic equations by the factorisation method:

`2/5x^2 - x - 3/5` = 0

Advertisement

#### Solution

Given equation is `2/5x^2 - x - 3/5` = 0

On multiplying by 5 on both sides, we get

⇒ `2x^2 - 5x - 3` = 0

`2x^2 - (6x - x) - 3` = 0 ....[By splitting middle term]

⇒ `2x^2 - 6x + x - 3` = 0

⇒ `2x(x - 3) + 1(x - 3)` = 0

Now `(x - 3)(2x + 1)` = 0

`x - 3` = 0

⇒ x = 3

And `2x + 1` = 0

⇒ `x = - 1/2`

Hence the roots of the equation`2x^2 - 5x - 3` = 0 are `- 1/2` and 3.

Is there an error in this question or solution?